Analisis Kadar Senyawa Rhodamin B Pada Sediaan Lipstik Menggunakan Metode Spektrofotometri UV-Vis - Faramita Hiola; Mahdalena Sy Pakaya; Juliyanty Akuba (State University of Gorontalo, 2021)
Rhodamine B is a syntheticdye use in paper, textile, and ink dyes. This compound can irritate the respiratory tract and cause cancer with liver damage. The present study aimed to find out the levels of rhodamine B contained in lipstick. It relied on qualitative and quantitative testing. The qualitative testing applied the thin-layer chromatography method with ethyl acetat eluent: n-buthanol : ammonia with the best ratio of 20:55:25. Meanwhile quantitative testing used the UV-Vis Specrophotometry method. It was shown from the quantitative test using thin-layer chromatography that three samples of lipstick contained rhodamine B. Further, the quantitative test with the UV-Vis spectrophotometry indicated that the levels of rhodamine B were measured at 6.62 µg/mL with 0.662%